The Participatory Mapping as Soft-Territorialization Discipline Practice of The Karen People in The Thailand Highlands - Wicaksono, Agung (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
Territorialization is an important element for the authorities to control both natural and human resources. Although the territorialization in Thailand has been started since the 1930s, but until the 2000s, the expected results are still far from satisfactory. One of the fundamental issues is the overlap of land claims, especially between the Royal Forestry Department (RFD) and the Karen people. In the midst of this cold war, the local government (TAO) is working with non-governmental organizations to encourage the implementation of participatory mapping. In this case, land cleared after 2014 must be submitted to the RFD for reforestation. Surprisingly, the program was a great success. This article seeks to explain why participatory mapping was a great success even though the program limited or even reduced Karen people's access to farmland. Based on ethnographic research and combined with map analysis, this study found that successful participatory mapping due to the presence of new, effective satellite-based surveillance instruments linked to the presence of relatively affluent farming households. Keywords: Karen, participatory mapping, shifting cultivation, smooth territorialization, territorialization